Colonialism, modernity, and literature : a view from India - Mohanty, Satya P. (Satya Prakash), 1954- (New York : Palgrave Macmillan, 2011)
"Mohanty has assembled an innovative volume of essays situated at th e intersection of at least three multi-disciplinary fields: postcolonia l and subaltern theory; comparative literary analysis, especially with a South Asian and transnational focus; and the study of "alternative" a nd "indigenous" modernities. Contributors emphasize the strategies of r esistance that are encoded in third world literary texts; comparative l iterary analysis, across cultures and regions - both within the "Global South" and beyond; the forms of indigenous modernity that preceded the colonial encounter, and thus provide alternatives to the modernity tha t was imposed through the colonial encounter with Europe; feminist pers pectives in traditional and contemporary literature; and "realist" theo retical analyses of the epistemic implications of literary forms. This definitive new work grounds the political insights of postcolonial and subaltern theory in close textual analysis, and rather than make genera l pronouncements about "alternative modernities," it looks at their spe cifically textual (literary and cultural) manifestations"--
Includes bibliographical references and index.
Keywords: Indic literature -- 20th century -- History and criticism; Colonies in literature; Imperialism in literature; Postcolonialism in literature; Postcolonialism -- India; India -- In literature